The Concept Of Accelerating National Development Through Quality Legal Products - Hari Purwoko; Ardian Sukma (International Asia Of Law and Money Laundering (IAML), 2022)
Quality legal products are the most important requirement in the process of national development of the state of Indonesia as a means of development in various lines can be achieved. However, so far, the number of legal products tested by the Constitutional Court (MK) indicates that legal products made by the Legislature and the executive still cannot be said to be of quality. It is necessary to strengthen and synergize legal products with the Constitution or the 1945 Constitution (1945 Constitution). This, can be pursued through the judicial branch of power, namely by the mechanism of preventive review by the Constitutional Court. The term preventive review is basically a mechanism for testing the constitutionality of draft laws (RUU) in the Constitutional Court which will test the bill before it is passed and enacted. Thus, the Constitutional Court as the guardian of the Constitution provides a preventive contribution to every legal product of legislation that is made, so that it can be in line with the ideals of the Constitution and give birth to quality legal products. This study is a doctrinal research that uses primary legal materials and secondary legal materials. The method used is juridical-normative approach using legislation and conceptual. The results of this study at least provide a conclusion that there is an urgency to increase the authority of preventive review by the Constitutional Court. Where, if this mechanism is applied, the legal products made are expected to be in line with the ideals of the Constitution so as to give birth to quality legal products which can then support and accelerate the development process in the state of Indonesia is achieved.